THE DESIGN PRINCIPLES OF LIQUIDATION ACTIVITIES OF SPILLS ON THE RAILWAY LINES - Zelenko, Yu. V.; Zhui, Chzhu; Pustovarova, T. M.; Yaryshkina, L. O. (Science and Transport Progress, 2008)
The principles and requirements to development of elimination measures after emergency emissions of dangerous freights are considered. The structure and mechanism of interaction of state and departmental divisions on elimination of accident aftermaths are presented.